Surrealist technique and the uncanny in the films of the quay brothers: A case study of Street of crocodiles 1986 and Rehearsals for extinct anatomies 1988 - Buck, Sascha (My University, 2014)
The Quay Brothers’ films have often provoked some kind of discomfort in the viewers. There are various techniques that the Quay Brothers utilise which cause this feeling of discomfort. This study is premised on the argument that the feeling that we experience while watching their films can be analysed through Sigmund Freud’s understanding of the uncanny. The feeling of the uncanny is brought about by various Surrealist techniques utilised by the Quay Brothers. This study focuses on the films Rehearsals for Extinct Anatomies and Street of Crocodiles by the Quay Brothers. Both these films strongly emphasise the use of Surrealist techniques as well as strongly evoking the feeling of the uncanny in the viewer.